Rezension von BECKER, Lidia, Julia Kuhn, Christina Ossenkop, Anja Overbeck, Claudia Polzin-Haumann & Elton Prifti (ed.). 2020. Fachbewusstsein der Romanistik. Romanistisches Kolloquium XXXII. Tübingen: Narr Francke Attempto. - Grutschus, Anke (apropos [Perspektiven auf die Romania], 2021)
Rezension